Boutique Healthcare : The Way forward for Not-for-profit Healthcare Organizations - John, Denny (Indian Journal of Marketing, 2007)
In India, provision of healthcare services is complex. At one level there is the public sector, which provides health services through the central government, state governments, municipal corporations and other local bodies. At the other level exists the private sector, which consists of the 'not-for-profit' and for-profit health sector. The not-for-profit health sector, which is very small, includes health services provided by NGOs, charitable institutions, missions, trusts, etc.